PERAN PEMERINTAH DAN PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DAERAH - Husnul Imtihan; Wahyunadi Dr; M Firmansyah (Trunojoyo University of Madura, 2017)
This study aims to determine the role of the Government and People's Participation in Development Planning in the District Gunungsari, especially on Musrenbang village, in the village of Taman Sari subdistrict Gunungsari West Lombok regency. This research method is a descriptive study with a qualitative approach, using qualitative data analysis interactive model. The results of this study prove that not maximal community participation in development planning and the role of government is still impressed elitist in the sense that it is the government that determines the development policy, while the public role to give advice to the government about what is needed by the community.